2006
DOI: 10.1103/physrevlett.96.018306
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Surface Reactions at a Spinning Wall

Abstract: We report a new method for studying surface reactions and kinetics at moderately high pressures (<10 Torr) in near real time. A cylindrical substrate in a reactor wall is rotated at up to 200,000 rpm, allowing the surface to be periodically exposed to a reactive environment and then analyzed by a triple-differentially pumped mass spectrometer in as little as 150 micros thereafter. We used this method to study oxygen plasma reactions on anodized aluminum. When the substrate is spun with the plasma on, a large i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…The difficulty lies not in the modeling of these processes but on the lack of rate constants for most species and the dependence of these on the materials used as electrode=targets, their surface condition and even the exposure time to the plasma. 31 This loss is discussed in Sec. V. The electron energy flux to the electrodes is given by 21,23 C e Á n ¼ 5 3 1 4 en e v th;e À e r c X C þ Á n ;…”
Section: Description Of the Modelmentioning
confidence: 99%
“…The difficulty lies not in the modeling of these processes but on the lack of rate constants for most species and the dependence of these on the materials used as electrode=targets, their surface condition and even the exposure time to the plasma. 31 This loss is discussed in Sec. V. The electron energy flux to the electrodes is given by 21,23 C e Á n ¼ 5 3 1 4 en e v th;e À e r c X C þ Á n ;…”
Section: Description Of the Modelmentioning
confidence: 99%
“…4 show a non-exponential decay with increasing t r . It was previously shown that this non-exponential behavior results from a mechanism in which O atoms recombine at differing rate on the surface at a distribution of sites [28,29,31]. The fast rate of recombination and desorption at short times indicates that a majority of surface sites are relatively efficient in recombining O, while the long tail is a result of the presence of a smaller fraction of sites where recombination is slower.…”
Section: Determination Of Recombination Coefficients Using the Spinnimentioning
confidence: 99%
“…Surface recombination reaction then leads to the formation and desorption of reaction products (e.g., O 2 ). These products can be detected either by an increase of the line-of-sight MS signal [28,29] or through a pressure rise measured with an ultrahigh-vacuum ionization gauge in the AES chamber [32]. The dominant reaction product measured by MS following exposure of the substrate to an O 2 plasma was O 2 at m/z = 32 [28].…”
Section: Determination Of Recombination Coefficients Using the Spinnimentioning
confidence: 99%
See 2 more Smart Citations